2014
DOI: 10.1371/journal.pone.0114218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trace Elements Mixture on Bacterial Diversity and Fermentation Characteristics of Liquid Diet Fermented with Probiotics under Air-Tight Condition

Abstract: Cu2+, Zn2+, Fe2+ and I− are often supplemented to the diet of suckling and early weaning piglets, but little information is available regarding the effects of different Cu2+, Zn2+, Fe2+ and I− mixtures on bacteria growth, diversity and fermentation characteristics of fermented liquid diet for piglets. Pyrosequencing was performed to investigate the effect of Cu2+, Zn2+, Fe2+ and I− mixtures on the diversity, growth and fermentation characteristics of bacteria in the liquid diet fermented with Bacillus subtilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Mantel test analysis revealed that the major deterministic factors causing trends in soil bacterial community composition are soil pH and to a slightly lesser extent Mg, Ca, TP, TK, and climate factors (MAP-mean annual precipitation, MAT-mean annual temperature; Additional file 2 : Tables S4 and S7). It is clear that various trace elements could influence the microbial diversity and community, such as the compound variable Cu/As/Ca [ 63 ], mixtures of Cu 2+ , Zn 2+ , Fe 2+ and I − [ 64 ], Fe [ 65 ] and Ca [ 66 ]. Taking Mg and Ca for example, Sagova-Mareckova et al found that the abundance of soil Actinobacteria was positively correlated with these two factors [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mantel test analysis revealed that the major deterministic factors causing trends in soil bacterial community composition are soil pH and to a slightly lesser extent Mg, Ca, TP, TK, and climate factors (MAP-mean annual precipitation, MAT-mean annual temperature; Additional file 2 : Tables S4 and S7). It is clear that various trace elements could influence the microbial diversity and community, such as the compound variable Cu/As/Ca [ 63 ], mixtures of Cu 2+ , Zn 2+ , Fe 2+ and I − [ 64 ], Fe [ 65 ] and Ca [ 66 ]. Taking Mg and Ca for example, Sagova-Mareckova et al found that the abundance of soil Actinobacteria was positively correlated with these two factors [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrients from animal manure inputs (such as poultry litter and cattle manure) are also excellent microbial food sources (Ashworth et al, 2017). Trace elements are also required for bacterial growth and act as cofactors for essential enzymatic reactions in bacterial cells (He et al, 2014). Therefore, increased nutrients from poultry litter applications and grazing likely promotes bacterial richness and diversity, although their combined effects are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The Bacillus subtilis fermented liquid diet contains more active components for the growth of lactic acid bacteria and a high lactic acid concentration 55 56 . These active components allowed lactic acid-producing bacteria to grow better in the intestines of piglets from the BFLD group than in the intestines of piglets from the BCPD group.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for PCR, pyrosequencing, sequence processing and bioinformatic analyses were previously described 56 59 . Differential metabolites were determined using gas chromatography time of flight mass spectrometry 55 .…”
Section: Methodsmentioning
confidence: 99%